Compressive strength of concrete mixtures of phosphorus powder and glass powder in concrete of grade FC'20 MPA - Hartanto, Adrian; Rini, Rini; Nasution, Ridwan (Trigin Publisher, 2024)
The research objective in this study is to analyze the effect of substitution of phosphorus powder and glass powder which has an impact on the compressive strength of 20 Mpa fc concrete and to find out the results of testing the compressive strength of concrete with added phosphorus and glass powder at ages 7 days, 14 days, 21 days and 28 days. From the research results, it was found that the compressive strength value of concrete aged 7 days in variations of 3% Glass concrete and 0.35% Phosphorus decreased compared to normal concrete with a ratio of 43%, in variations of Glass concrete 5% and 0.35% Phosphorus decreased compared to normal concrete with a ratio 53% and in the Glass concrete variation 7% & 0.35% Phosphorus decreased to 45.5%. At the age of 14 days in the Glass concrete variation of 3% and 0.35% Phosphorus decreased compared to normal concrete with a ratio of 26%, in the Glass concrete variation of 5% and 0.35% Phosphorus decreased compared to normal concrete with a ratio of 21% and in the Glass concrete variation 7% & 0.35% Phosphorus decreases up to 20%. At 21 days, the Glass concrete variation of 3% and 0.35% Phosphorus increased compared to normal concrete with a ratio of 6.5%, the Glass concrete variation of 5% and 0.35% Phosphorus decreased compared to normal concrete with a ratio of 6% and the Glass concrete variation 7% & 0.35% Phosphorus decreases up to 11%. At 28 days in the Glass concrete variation of 3% and 0.35% Phosphorus increased compared to normal concrete with a ratio of 1.10%, in the Glass concrete variation of 5% and 0.35% Phosphorus decreased compared to normal concrete with a ratio of 0.95% and in the Glass concrete variation 7 % & 0.35% Phosphorus decreased to 18.02%.